Identifying the key sectors in the carbon emission flows along the production chain paths: A network perspective. (November 2021) - Jiang, Meihui; An, Haizhong; Gao, Xiangyun; Zheng, Huiling; Li, Yu
Highlights: We built a carbon-flow-based production chain network. We proposed five new indicators to measure the importance of sectors. We identified the key sectors in the production chains in China. Abstract: Effectively reducing carbon emissions is a serious issue faced by many countries. Identifying key sectors in terms of carbon emissions in production activities is vital for policy-making regarding energy related carbon emission reductions. This paper built a carbon-flow-based production chain network and proposed five indicators, including direct outflows, direct inflows, self-flows, indirect outflows and indirect inflows of carbon emissions, to quantify the importance of sectors to carbon emissions. The results showed that there were no strong correlations among the different roles of sectors. This independence of sectoral roles indicated that it was necessary to measure the importance of sectors from different perspectives. The results also showed that a few sectors played important roles in carbon emission flows. It indicated that the growth of carbon emissions in China was direct and indirectly driven by a few key sectors. Finally, the results of clustering analysis showed the clusters exhibited significantly different features. Commonly, industries processing primary products played core roles in production chains. Most industries processing deep-processing products had strong inflows of carbon emissions. Such information provides a valuable reference to make carbon reduction policies according to the roles of sectors in the production chains.